Synthesis and characterization of high density polyethylene/peat ash composites. (1st June 2016) - Cao, Zhi; Daly, Michael; Geever, Luke M.; Major, Ian; Higginbotham, Clement L.; Devine, Declan M.
Abstract: A new type of polymer composite was synthesized from peat ash which was obtained as industrial waste. This was added to high density polyethylene (HDPE) at varying mixing ratios and the resulting products were characterized using different experiments which included Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), melt flow index (MFI), density, wettability, tensile test, flexural test and cost analysis. The effects of various ash loadings and the use of the maleic anhydride grafted high density polyethylene (HDPE-g-MA) compatibilizer on the physical and mechanical properties of composites were investigated. It was observed that the utilization of peat ash significantly increased the tensile strength and the flexural modulus, where also reducing raw material cost. Incorporating (HDPE-g-MA) in the composites formulation led to further increases in tensile and flexural properties. Conversely, there was a significant decrease of impact strength found for all composites in comparison to the virgin HDPE. And the impact strengths generally decreased as peat ash content increases. Microstructural analyses showed that surface treated peat ash particles appeared to be well-incorporated into the HDPE matrix, as intimated polymer/peat ash contact was observed. In addition, the melt flow index of the composites decreased remarkably with an increase in peat ash content. No significant water uptake effect was detected on peat ash composites indicating that these materials could be used as a direct replacement for HDPE in applications where impact strength is not a critical factor. Furthermore, the use of peat ash increased the composite density in comparison to virgin HDPE. Nevertheless, as peat ash reinforcement does offer increased tensile and flexural properties, this may make the end product lighter as lower wall thickness parts can be used to fulfil the same function. From this study, it was concluded that the utilization of the peat ash from peat fired power stations has proved to have significant value-added potential as a filler material in polymer composites.